ANTECEDEN TERHADAP PENYERAPAN ANGGARAN BELANJA (Studi pada Satuan Kerja Badan Penelitian dan Pengembangan Kesehatan) - Ayu Made Rai Astuti, Ida; Sadeli, Dadang; Hidayat, Nur (SEKOLAH PASCASARJANA PRESS, 2018)
The study aims to find out impacts of budget plan, budget implementation and internal control to budget absorption in Badan Litbangkes. The samples for this study are 112 informants from 16 working units. Data analysis was done using quantitative method with survey approach. The conclusion from partially tested variable is that budget plan and internal control variables are significantly influent to budget absorption. On the other hand, budget implementation does not significantly influent to budget absorption. Based on simultaneous test, all independent variables, significantly influent to budget absorption. This research is expected to provide solutions for better preparation of planning and managing finance.